Didactic Concept of Learners as Designers in Teaching German as a Foreign Language - Katarina Krželj; Sonja Urošević; Saša Podgoršek (University of Belgrade, Teacher Education Faculty, 2021)
This paper deals with the didactic concept of Learners As Designers (Jonassen and Reeves, 1996) which is based on the assumption that digital media have the potential to accompany, support, and complement the learning process as a cognitive tool, to enable active knowledge construction and transfer, and to change the role of learners in the classroom. The events triggered by the pandemic have reinforced the need for distance learning, which requires the ability to work autonomously, to further develop learning strategies supported by digital tools, and to develop key competencies. The study aimed to determine the potential of the Learners As Designers concept to motivate students to learn autonomously, apply new vocabulary learning strategies supported by digital tools, and improve their digital literacy. The study was conducted in 2019/2020 among 78 students of German for Specific Purposes at the University of Belgrade, Singidunum University Belgrade, Serbia, and University of Ljubljana, Slovenia. The students used the digital tool Quizlet to consolidate lexical items. Data were collected through a questionnaire with open and closed questions. The results of the quantitative analysis showed that students spend more time on vocabulary learning than before. The qualitative analysis reflects their opinion that they learned more and were motivated because of the opportunity to create learning material autonomously and collaboratively. There is also a trend of increased vocabulary learning frequency, especially with the support of digital tools.